Lysophosphatidic Acid Enhanced the Angiogenic Capability of Human Chondrocytes by Regulating Gi/NF-kB-Dependent Angiogenic Factor Expression - Chuang, Yi-Wen; Chang, Wen-Ming; Chen, Kai-Hua; Hong, Chang-Zern; Chang, Pey-Jium; Hsu, Hung-Chih (PLOS ONE, 2014)
Lysophosphatidic acid (LPA) has been found to mediate myeloid differentiation, stimulate osteogenesis, alter cell proliferation and migration, and inhibit apoptosis in chondrocytes. The effect of LPA on the angiogenic capability of chondrocytes is not clear. This study aimed to investigate its effect on the angiogenic capability of human chondrocytes and the underlying mechanism of these effects. Human chondrocyte cell line, CHON-001, commercialized human chondrocytes (HC) derived from normal human articular cartilage, and human vascular endothelial cells (HUVECs) were used as cell models in this study. The angiogenic capability of chondrocytes was determined by capillary tube formation, monolayer permeability, cell migration, and cell proliferation. An angiogenesis protein array kit was used to evaluate the secretion of angiogenic factors in conditioned medium. Angiogenin, insulin-like growth factor-binding protein 1 (IGFBP-1), interleukin (IL)-8, monocyte chemoattractant protein-1 (MCP-1), matrix metalloproteinase (MMP)-9, and vascular endothelial growth factor (VEGF) mRNA and protein expressions were evaluated by Q-RT-PCR and EIA, respectively. LPA receptor (LPAR) expression was determined by RT-PCR. Signaling pathways were clarified using inhibitors, Western blot analysis, and reporter assays. The LPA treatment promoted the angiogenic capability of CHON-001 cells and HC, resulting in enhanced HUVEC capillary tube formation, monolayer permeability, migration, and cell growth. Angiogenin, IGFBP-1, IL-8, MCP-1, MMP-9, and VEGF mRNA and protein expressions were significantly enhanced in LPA-treated chondrocytes. LPA2, 3, 4 and 6 were expressed in CHON-001 and HC cells. Pretreatment with the Gi/o type G protein inhibitor, pertussis toxin (PTX), and the NF-kB inhibitor, PDTC, significantly inhibited LPA-induced angiogenin, IGFBP-1, IL-8, MCP-1, MMP-9, and VEGF expressions in chondrocytes. The PTX pretreatment also inhibited LPA-mediated NF-kB activation, suggesting the presence of active Gi/NF-kB signaling in CHON-001 and HC cells. The effect of LPA on the angiogenesis-inducing capacity of chondrocytes may be due to the increased angiogenesis factor expression via the Gi/NF-kB signaling pathway.